A Spatial Evaluation of Healthy Food Access: Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Participants. (September 2019) - Davis, Jonathan; Jossefides, Mindy; Lane, Travis; Pijawka, David; Phelps, Mallory; Ritchey, Jamie
Abstract : Context: It is well known in public health practice that vulnerable populations in rural and inner-city areas may not be able to access healthy foods due to cost, availability, access to transport, and other factors. Program: The Inter Tribal Council of Arizona, Inc (ITCA), Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides moderate- and lower-income families with increased access to nutritional information, health care, and healthy foods. Implementation: ITCA WIC authorizes and enters into contracts with stores that carry a baseline of healthy foods. To use WIC benefits, participants must go to authorized WIC stores where approved healthy foods are available. Evaluation: ITCA Tribal Epidemiology Center developed a methodological framework using Geographic Information Systems to examine WIC authorized stores in 2014 and 2016 to determine whether there were gaps in the store network. To be considered served by the store network, urban WIC participants were required to be within 1 mile and nonurban WIC participants were required to be within 5 miles of a store. We examined whether additional stores could be added to the network to decrease travel distance and travel time in order to further improve access to healthy foods. Discussion: Between 2014 and 2016, 700 stores were examined and WIC authorized 8 new stores to increase the network; all remote and most rural stores were WIC authorized. In 2014, about 50% of participants met the criteria to be considered served. In 2016, 54% met the criteria, indicating a modest increase in store access for WIC participants. Store network access increased in urban areas from 39% to 41% and from 66% to 74% in nonurban areas between 2014 and 2016. By evaluating the ITCA WIC authorized stores, we note that ITCA increased access to WIC approved healthy foods for WIC participants.